CYTOTOXIC AND ANTIOXIDANT PROPERTIES OF FRACTIONS ISOLATED FROM FERONIA ELEPHANTUM - Nattudurai, G.; Balachandran, C.; Paulraj, M. Gabriel; Duraipandiyan, V.; Ignacimuthu, S.; Dhabi, N. A. Al (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The leaves of Feronia elephantum are widely used in folk medicine in India to treat various ailments. In the present communication we report the cytotoxic and antioxidant properties of extracts and fractions of F. elephantum leaves. Methods: The leaves of F. elephantum were extracted with hexane and ethyl acetate and checked for cytotoxic properties against human A549 lung adenocarcinoma cancer cell line. The active extract was subjected to column chromatography and fractions were bio-assayed. The active fraction was subjected to GC-MS analysis. Results: Hexane extract exhibited good cytotoxic activity against A549 lung cancer cell line compared to ethyl acetate extract. Hexane extract showed 77.3% activity at the dose of 500 µg/mL with IC50 (50.6%) value of 125 µg/mL. Hexane extract was also tested at different time intervals of 12h, 24h, 48h and 72 h. The activity gradually increased. The active hexane extract was subjected to column chromatography. Based on thin layer chromatography profiles, similar fractions were combined to give 9 fractions. When the fractions were bio-assayed fraction 5 showed maximum cytotoxic activity. Fraction 5 was tested against A549 lung cancer cell line at different time intervals; the activity gradually increased. Fraction 5 was used to test the antioxidant properties using DPPH analysis. Maximum antioxidant activity was observed at 1000 µg/mL (71.63 ± 0.15). Active fraction 5 was identified using GC-MS. It showed the presence of Estragole (50.82%), trans-anethole (p-propenylanisole, anise camphor) (14.98%) and Caryophyllene (9.22%). Conclusion: The results showed that hexane extract of F. elephantum could be probed further in drug discovery programme.